Therapeutic Strategies to Target Calcium Dysregulation in Alzheimer’s Disease - Maria Calvo-Rodriguez; Elizabeth K. Kharitonova; Brian J. Bacskai (Cells, 2020)
Alzheimer’s disease (AD) is the most common form of dementia, affecting millions of people worldwide. Unfortunately, none of the current treatments are effective at improving cognitive function in AD patients and, therefore, there is an urgent need for the development of new therapies that target the early cause(s) of AD. Intracellular calcium (Ca2+) regulation is critical for proper cellular and neuronal function. It has been suggested that Ca2+ dyshomeostasis is an upstream factor of many neurodegenerative diseases, including AD. For this reason, chemical agents or small molecules aimed at targeting or correcting this Ca2+ dysregulation might serve as therapeutic strategies to prevent the development of AD. Moreover, neurons are not alone in exhibiting Ca2+ dyshomeostasis, since Ca2+ disruption is observed in other cell types in the brain in AD. In this review, we examine the distinct Ca2+ channels and compartments involved in the disease mechanisms that could be potential targets in AD.